Waste capacity and its environmental impact of a residential district during its life cycle - Hatice Sözer; Hüseyin Sözen (Energy Reports, 2020)
Buildings generate a significant amount of waste that has considerable impacts on environment and energy flow. This study aims to investigate the waste capacity of the selected district and its effect on the environment within the current waste management policy via Life Cycle Assessment (LCA) methodology based on the two indicators; global warming potential and energy flow. The district has 82 buildings with 64,971m2 total gross area and 2,000 populations. Accordingly, the district's waste capacity was evaluated within the classification of Municipal Solid Wastes (MSW), liquid wastes, and demolition wastes. The system boundaries of the LCA were set based on the gate-to-grave approach, which includes generated wastes during the lifespan of the buildings, including their end-of-life stage. Consequently, energy recovery potentials from waste processes were investigated and compared with the primary energy demand of the operational energy consumption of the buildings to perceive the amount of energy compensation range. Additionally, buildings' physical conditions, which obtained from their Building Information Models (BIM), energy performances, derived from their energy models and local specifications, obtained from standards were utilized to identify the current conditions and waste management systems. Critically, the outcomes of all those were used as input data for the LCA model. The results showed that there had been energy recovery potentials from MSW's treatments, while liquid wastes and demolishing wastes treatments have consumed energy. Energy recovery potential from MSW has compensated only 5.8% of operational energy annually, which came from recycling processes. Also, all waste management systems release greenhouse gases to the atmosphere that cause global warming.
Keywords: 330; Life cycle assessment; Municipal solid waste; Demolition waste; District-scale waste management; Liquid waste; Waste capacity